Indians, alcohol, and the roads to Taos and Santa Fe - Unrau, William E., 1929-2016 (University Press of Kansas, 2013)
Santa Fe Trail Association Award of MeritIn the culture of the American West, images abound of Indians drunk on the white man's firewater, a historical stereotype William Unrau has explored in two previous books. His latest study focuses on how federally-developed roads from Missouri to northern New Mexico facilitated the diffusion of both spirits and habits of over-drinking within Native American cultures. Unrau investigates how it came about that distilled alcohol, designated illegal under penalty of federal fines and imprisonment as a trade item for Indian people, was nevertheless easily obt.